Cyanide Analysis Of Mining Effluents By Specific Ion Electrode - Robert M. Mann (Society for Mining, Metallurgy & Exploration, 1981)
The Ag/S specific ion electrode has been evaluated for analysis of both free and total cyanide. Metal cyanide solutions were prepared from reagent grade compounds and by stoichiometric fixture of the metal with a potassium cyanide solution. Solutions containing Cu+1, Ni+2, Fe+2, Fe+3 and Zn+2 complexes were analyzed prior to and following EDTA pre treatment. This effort provides an understanding of the effect of each metal cyanide complex on the SIE analysis of free and "total" cyanide.